Risk Factor Analysis of Influence of Diet on Incidence of Anemia - Ananda, Asti; Cholidah, Rifana; Amalia, Emmy (Jurnal Biologi Tropis, 2025)
Anemia is a global health problem affecting approximately one-quarter of the world's population and remains a major concern in Indonesia, particularly among adolescents and young adults. University students, as part of the young adult group, are at risk of developing anemia due to several factors, especially unhealthy dietary patterns, unbalanced diets, and insufficient intake of macro- and micronutrients essential for hemoglobin synthesis. This study aims to examine the relationship between dietary patterns and the incidence of anemia among university students, particularly medical students. This research employed a literature review method using purposive sampling from PubMed, Google Scholar, and ScienceDirect databases, with the keywords “dietary patterns” and “anemia.” A total of 24 relevant articles in both Indonesian and English were analyzed descriptively. The findings indicate a significant relationship between dietary patterns and anemia. Low consumption of iron, vitamin B12, and folate, along with habits such as skipping breakfast, are associated with a higher risk of decreased hemoglobin levels. Several studies demonstrated a significant correlation between dietary quality and anemia, although some reported inconsistent results.